Electromagnetic-deformational waves of the Earth crust - V.N. Uvarov (Геофизический журнал, 2016)
This article briefly analyzes mechanisms of mechanoelectromagnetic transformations of the earth’s crust. It demostrates that the presence of these effects leads to the appearance of electromagnetic satellites, which are secondary electromagnetic waves associated seismic and acoustic waves propagating at the speed of the acoustic waves. The result is electromagnetic deforming wave, whose parameters depend on the source of excitation and parameters of propagation environment. Here is a proof of this phenomenon, gained during the field experiment conducted with the use of a borehole in a seismically active region of Kamchatka. It is concluded that the existence of 1) electromagnetic deforming waves is one of the fundamental properties of the Earth’s crust, 2) parameters of electromagnetic deforming waves depend strongly on the nature of the excitation source and the properties of the propagation medium